2016
DOI: 10.1073/pnas.1515480113
|View full text |Cite
|
Sign up to set email alerts
|

LDL receptor-related protein-1 regulates NFκB and microRNA-155 in macrophages to control the inflammatory response

Abstract: LDL receptor-related protein-1 (LRP1) is an endocytic and cellsignaling receptor. In mice in which LRP1 is deleted in myeloid cells, the response to lipopolysaccharide (LPS) was greatly exacerbated. LRP1 deletion in macrophages in vitro, under the control of tamoxifen-activated Cre-ER T fusion protein, robustly increased expression of proinflammatory cytokines and chemokines. In LRP1-expressing macrophages, proinflammatory mediator expression was regulated by LRP1 ligands in a ligand-specific manner. The LRP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
162
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(174 citation statements)
references
References 50 publications
(65 reference statements)
9
162
1
2
Order By: Relevance
“…PDCD4 and miR-155 played important roles in the regulation of inflammation response [24, 3335]. Three PDCD4 siRNA oligos were transfected into RAW264.7 cells to evaluate the suppression effective of PDCD4 expression.…”
Section: Resultsmentioning
confidence: 99%
“…PDCD4 and miR-155 played important roles in the regulation of inflammation response [24, 3335]. Three PDCD4 siRNA oligos were transfected into RAW264.7 cells to evaluate the suppression effective of PDCD4 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Although the specific LRP1 ligands that mediate the inflammatory responses remain to be identified, our results suggest that RAP may inhibit the binding of ligands to LRP1 and therefore trigger microglial activation. Indeed, a previous study has shown that the LRP1 agonist attenuated the expression of pro-inflammatory mediators even in the presence of LPS, while the antagonist and LRP1 antibody that block its function had an opposite effect in macrophage [56]. Identifying specific LRP1 ligands that are involved in the regulation of microglial activation might provide a novel target for AD therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, our group and others have shown that LRP1 also regulates the activation of the inflammatory NF-κB signaling pathway 134,137 . In this work, I show for the first time that LRP1 can inhibit the MyD88 pathway downstream of the TLR signaling pathways.…”
Section: How Does Lrp1 Inhibit Nf-κb?mentioning
confidence: 82%
“…In a sepsis model of LPS injection, peripheral macrophage LRP1 deficient animals showed decreased survival rates and corresponding increased systemic amounts of circulating TNFα and CCL3 137 . There was also increased IL-6 and iNOS mRNA 27 expressed in the organs of these mice.…”
Section: Lrp1 Function: Inflammationmentioning
confidence: 98%
See 1 more Smart Citation